Globalization, development and security in Asia : Volume 4 / Editor-in-Chief Zhiqun Zhu Bucknell University, USA - Jieli Li (World Scientific, 2014)
"Asian countries are undergoing rapid political, economic and social transformations; meanwhile, there is a growing demand for knowing more about Asia. This major reference set is designed to help general readers as well as specialists to have a good grasp of the latest developments in Asia in the key areas of economic growth, trade, energy, environment, foreign policy and security. With 4 volumes, this set covers all major dimensions of Asia's political economy. Contributors include both scholars and practitioners who provide first-hand description and analysis of fundamental issues in Asia. Volume 2 studies the strong economic integration through trade and cross-border investment that has been essential to Asia. The region's future prosperity depends on it being able to remain open and outward-looking. As Asia grows larger and richer, more concerted efforts are required to surmount regional rivalry and to further strengthen the regional architecture of economic cooperation. Volume 3 looks at the emerging economies' thirst for energy that creates huge competition, around which domestic, regional, and international political economy unfolds. Climate change and aspiration for sustainable development further complicate the challenge. Volume 4 offers a comprehensive coverage of subjects on environment and sustainable development in Asia with case studies of selected and representative countries that are at different stages of economic development and facing different environment-related problems and challenges in the twenty-first century"--